CORRELATION BETWEEN SMARTPHONE USAGE DURATION AND HANDGRIP STRENGTH IN ADOLESCENTS AGED 18-24 IN TULUNGAGUNG - Aloysius Ivander Wirayudha Widjaja; Gede Parta Kinandana; Agung Wiwiek Indrayani; Ni Komang Ayu Juni Antari (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2022)
Generally, a person will spend quite a long time using his smartphone. Prolonged use of smartphones can cause musculoskeletal disorders. This event can make the function of the biomotor component decrease. One of the decreased biomotor components is handgrip strength. The role of physiotherapy is needed to educate in avoiding the risk of decreased grip strength. Therefore, this study aims to determine the relationship between smartphone usage duration with handgrip strength in adolescents aged 18-24 years. This research is an analytical observational study using a cross-sectional approach. Sampling using a purposive sampling technique. Fifty women aged 18-24 years who had met the participating criteria were the participants in this study. Handgrip strength was measured using a Camry Handgrip Dynamometer. Smartphone usage duration was obtained from recording the average daily screen time for a month. The average smartphone usage duration the participant's smartphone was 453.88 ± 159.16 minutes. Based on pearson correlation analysis, there is a significant negative relationship weak to moderate strength between smartphone usage duration and handgrip strength (r=-0.51; p=0.00 dominant handgrip, r=-0.33; p=0,02 non-dominant hand grip). Linear regression showed variations in the strength of the dominant handgrip as much as 26.4% and the non-dominant hand grip as much as 11% can be explained by the smartphone usage duration (p<0.05). The conclusion is smartphone usage duration is correlated with a decrease in handgrip strength. The longer using a smartphone, the weaker the grip strength. Keywords: screen time, smartphone, grip strength